Application of nano-refrigerant for boiling heat transfer enhancement employing an experimental study. (October 2019) - Sheikholeslami, M.; Rezaeianjouybari, Behnoush; Darzi, Milad; Shafee, Ahmad; Li, Zhixiong; Nguyen, Truong Khang
Highlights: Boiling heat transfer in a flattened tube is investigated experimentally. Nano-refrigerant (R600a/oil/CuO) is involved in current study. As mass flux and vapor quality augment, heat transfer rate enhances. h enhances with rise of H ∗, ϕ . Abstract: This research presents the outputs for nano-refrigerant (R600a/oil/CuO) boiling heat transfer within flattened channels utilizing experimental method. The influence of flattened percentage, flow rate, vapor quality as well as the mass fraction of CuO on boiling heat transfer (h) were discussed. Outcomes reveal that increasing the flattened percentage enhances the h . Also, within the ranges of present experiment, h augments by increasing nanoparticle's concentration.